Sosialisasi Pembelajaran STEAM Guna Meningkatkan Kreativitas Anak Usia Dini di Kecamatan Rejotangan, Kabupaten Tulungagung, Provinsi Jawa Timur - Laela Lutfiana Rachmah; Raras Ayu Prawinda; Devi Candra Nindiya; Umi Nahdiyah (Lifelong Education Journal, 2023)
Learning in AUD must be able to develop various basic abilities of children to create generations that are communicative, collaborative, think critically, creatively and innovatively. The STEAM approach is seen as an approach that can prepare the 21st century generation which aims to stimulate creativity, prepare children for a world of work full of innovations and inventions or good quality human resources. Some research shows that the application of the STEAM approach has a very positive relationship between STEAM learning experiences at an early age and school and career success in a child's future. The purpose of implementing this community service is to find out the application of learning with STEAM learning to increase the creativity of early childhood in Rejotangan District, Tulungagung Regency. This type of research is qualitative with descriptive method. Data collection was done by way of interviews and observation. The STEAM approach process is expected to be able to stimulate children's abilities to face the 21st century. One of the ways that teachers can do this is by changing the learning process in an innovative and creative way.